Pouvoir parler des pesticides ? Une recherche-action pour éprouver les capabilités des travailleurs viticoles (Gironde, France) - Ludovic Ginelli; Jacqueline Candau; Agossè Nadège Degbelo; Camille Noûs (VertigO)
In France, the intense public debate on pesticides is still hardly accessible to agricultural workers, even though they are expected to change their practices and are highly exposed. This configuration of pesticide use "transition" raises health, environmental and social justice issues, as do specific social movements, such as Environmental Justice in the United States or "ecologism of the poor" in the South (Martinez-Alier, 2014). We hypothesize that the weak voice of farmworkers in the public space is a sign of hindered capabilities (Sen 2000, de Munck 2008). Whether they are employees or farmers participating in winegrowing work, our research aims to identify the social processes, sometimes different, that strengthen or weaken their capabilities to express their concerns about pesticides. We test this hypothesis using an original methodological choice, an action-research committed to empowering vineyard workers in Gironde. It turns out that "strong" frames (risk management and occupational health policies) make it impossible for workers to express their concerns about pesticides. Other structural factors on the scale of the territory and the wine sector mean that the silencing of workers is dominant without being total. The "operational" difficulties in setting up a group of winegrowers, and even more so for the employees, are therefore particularly revealing of these antagonistic processes of (in)capacity at play in the transition to pesticides.